Digital Transformation and Skills Needed in The Area Of Artificial Intelligence - Based Accounting - Gabriela STAFIE; Veronica GROSU (Communications of International Proceedings, 2022)
Accounting, as it is now known, is the result of a long historical process marked by a series of transformations generated by technical progress. The accounting system has undergone a number of changes over time, and the digital age has led to the use of the traditional system as little as possible, bringing beneficial improvements to the accounting and financial industry. Although double-entry accounting has been used for centuries, the impact of the digital age requires a shift to triple-entry accounting based on blockchain technology. The penetration of technologies based on artificial intelligence in accounting, such as expert system, machine learning, automation of processes through robotics or blockchain, can add value to accounting activities by reducing errors and increasing the efficiency of accounting and financial processes. Therefore, the main objective of this paper is to analyze the current debates on the digital transformation of accounting, by reviewing the recent literature. The Web of Science (WoS) and Scopus databases were used in the data processing.
Keywords: digital accounting; process automation through robotics; artificial intelligence; blockchain